An in vitro comparison of the fracture resistance of standard and modified mesio-occluso-distal cavity designs restored with resin composite restoration - Al-Thobity, Ahmad M; Altaher, Abdulmalik; Alharbi, Abdullah; Elnour, Mutasim (International Journal of Health Sciences, 2018)
Objectives: The main goal of this study was to evaluate the fracture resistance of maxillary second premolar teeth with standard and conservative MOD cavity designs. Methods: Sixty maxillary second premolars were randomly divided into 6 Groups of 10 teeth. G1 consisted of intact teeth. G2 were prepared with separated proximal boxes that were designed to be 1 mm approximately above the CEJ for the cervical margins. The occlusal outline of the proximal was performed as approximately half of the intercuspal distance buccolingually and one-third of the mesiodistal dimension. The proximal preparation was standardized in all tested groups. G3 was prepared with an occlusal extension that extended approximately one third of bucculingual width and 2mm in depth. G4 was prepared with occlusal extension of 1mm in depth and width. G5: the occlusal extension was 1mm in depth and 2mm in width. G6: the occlusal extension was 2mm in depth and 1mm in width. Samples were restored with composite resin and subjected to load to failure testto evaluate the fracture resistance. Results: G1 showed the highest fracture resistance value (1737.1 N) while G3 had the lowest mean value (522.9 N). Furthermore, the fracture resistance of G4 and G5 was significantly higher than G3 and G6 (p< 0.05) where in both groups the preparation of the occlusal extension mostly remained in the enamel layer. Conclusion: Modified MOD cavity designs with 1mm depth in the enamel layer havesignificantly higher fracture resistance than the standard MOD cavity.